Effective Air Traffic Control Learning: New Approaches and Innovative Methods - Rinaldi, Ridho; Soeadyfa, Dimas Arya; Utomo, Wasito (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research discusses more effective Air Traffic Control (ATC) learning through new approaches and innovative methods. The new approaches described include project-based, problem-based, skill-based, and game-based approaches. Meanwhile, the innovative methods discussed include simulation, virtual reality (VR), and augmented reality (AR). Factors that influence the effectiveness of ATC learning are also discussed, including the ability of instructors, facilities, and student motivation. This research used qualitative methods by conducting interviews with 10 ATC personnel and 10 ATC instructors, and performing a Two Sample Mean Test on 96 ATC students in Indonesia. Based on the analysis, it was found that innovative methods and new approaches can improve the effectiveness of ATC learning compared to Conventional methods. However, further research is needed to deepen the use of technology in ATC learning.